The perspectives of clinical level medical students on animal-assisted therapy: a study in Ghana - Evans Paul Kwame Ameade; Linda Ama Owusuaa Amoah; Benjamin Yeboah Ofori (BMC, 2024)
Abstract Background The role of animal-assisted therapy (AAT) in complementary and alternative medicine is well acknowledged. AAT is widely patronized, in developed countries such as USA, Canada, and many European countries, but less so in developing countries in Africa including Ghana. For persons in developing African countries and elsewhere to benefit from AAT, healthcare professionals must be acquainted with it recommend it to their patients when necessary. This study therefore assessed the perspectives of clinical-level medical students on AAT. Method A semi-structured questionnaire was used to collect data in a cross-sectional study from 206 randomly selected clinical-level medical students of the University for Development Studies, Tamale, Ghana. The data was analyzed using Microsoft Excel and SPSS (Version 26) and the results were presented in Tables and charts. The association between demographic variables and the knowledge and attitude of the students were determined using ANOVA, while bivariate Pearson's correlation was used to measure the relationships between continuous variables. Associations were considered significant when p-value < 0.05. Results The knowledge about AAT among the medical students was very poor (0.971 ± 2.407 over 10; 9.7%); almost all of them (≈ 99.0%) had very little or no exposure to AAT in school or at home. The attitude of the students was however averagely positive (3.845 ± 0.748 over 7; 54.9%), with a perceived health benefit of ATT score of 4.768 ± 1.002 (68.1%). The motivation of the students to acquire more knowledge and skills about AAT mostly through lectures and practical sessions (70.9%) was good (4.809 ± 1.221; 68.7%). Female students were significantly more knowledgeable about AAT than their male counterparts (1.5 versus 0.6; p-value = 0.006). No other sociodemographic characteristics had any significant association with knowledge, attitude, and perception of benefit variables. However, a significant positive relationship was found to exist between the students' knowledge, attitude and perception of animal-assisted therapy (r ≥ 0.236; p-value ≤ 0.001). Conclusion We conclude that the knowledge about AAT among medical students is inadequate and this is worrying given the beneficial complementary role of AAT in achieving SDG 3. Medical schools and their regulators in Ghana should incorporate complementary and alternative medicine (CAM) lessons in their training curricula. For practising medical doctors, topics on CAM should be discussed during their Continuous Professional Development sessions. With better knowledge, physicians would possibly be more willing and confident in recommending this useful complementary and alternative medicine to patients who may seek other forms of therapy besides conventional medicine or which will augment the orthodox medication the patients may have been using to treat their conditions.